DESCRIPTION OF SLEEP QUALITY IN PREGNANCY AT MIDWIFERY HEALTH CARE MARGAJAYA CENTER OF LAMPUNG 2024 - LENI, MARLENI LENI (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2024)
Background: Sleep quality is an individual's ability to stay asleep and to get the right amount of sleep. According to the World Health Organization (WHO), the global prevalence of insomnia, which is a sleep disorder and sleep quality, in pregnant women throughout the world is 41.8%. The aim of the research is to determine the description of sleep quality in pregnant women at the Independent Midwife Practice in Margajaya, Central Lampung.. Method: This type of research is descriptive with a cross-sectional design. The population of this study was 112 pregnant women with a sample size of 88 respondents. The sampling technique uses purposive sampling. Results: The subjective sleep quality of pregnant women was in the very good category for 15 respondents (17.04%), quite good for 25 (28.40%), quite bad for 25 (28.40%), and very bad for 23 respondents (26.16%). Sleep duration > 7 hours 18 respondents (20.45%), sleep duration 6-7 hours 22 respondents (25%), sleep duration 5-6 hours 28 respondents (31.81%), and sleep duration <5 hours 20 respondents (22.74%) Conclusion: The majority of pregnant women in this study had quite good subjective sleep quality with an average sleep duration of 5-6 hours. It is hoped that PMB can provide promotive and preventive education. So, pregnant women can pay more attention to the condition of their pregnancy. Also, it can provide additional information for subsequent research in conducting similar research involving other variables.